Development and validation of the thyroid cancer self-perceived discrimination scale to identify patients at high risk for psychological problems - Liu, Zhi-jin; Feng, Lin-sen; Li, Feng; Yang, Li-rong; Wang, Wan-qi; He, Yuan; Meng, Zong-ting; Wang, Yu-feng (Frontiers in Oncology, 2023)
Objective: To develop a Thyroid Cancer Self-Perceived Discrimination Scale (TCSPDS) to identify patients at high risk for psychological problems and to test its reliability, validity and acceptability.: Using classical test theory, a total of 176 thyroid cancer patients from November 2021 to October 2022 were recruited to develop the TCSPDS. Item analysis was used to improve the preliminary TCSPDS. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and structural equation model (SEM) were used to test the construct validity of the final TCSPDS. Pearson correlation coefficient was used to analyze the validity coefficient between TCSPDS and EORTC QLQ-C30 to test the criterion-related validity (CRV) of the final TCSPDS. The internal consistency coefficient (Cronbach's alpha coefficient), split half reliability (Spearman-Brown coefficient) and test-retest reliability were used to verify the reliability of the final TCSPDS. The questionnaire completion time and effective response rate were used to validate the acceptability of the final TCSPDS.The TCSPDS consisted of 20 items and was divided into 3 subscales: 8 items for stigma, 6 items for self-deprecation, and 6 items for social avoidance. The TCSPDS had good validity (χ 2 /df=1.971, RMSEA=0.074, GFI=0.921, CFI= 0.930, IFI=0.932, TLI=0.901, Validity coefficient=0.767) , reliability (Cronbach's alpha=0.867, Spearman-Brown coefficient=0.828, test-retest reliability coefficient=0.981) and acceptability [average completion time (15.01±1.348 minutes) and an effective response rate of 95.14%]. Patients with higher TCSPDS scores reported a lower quality of life (P<0.05).The TCSPDS could be used for early identification and assessment of the level of self-perceived discrimination in patients with thyroid cancer, which may provide a scientific basis for health education, social support and psychosocial oncology services in the future, especially in Southwest China.